Arte e revolução: caminhos para a emancipação social em Herbert Marcuse - Carvalho, Caroline Mendes de (2010)
The ways Marcuse points out to the emancipation of society are the study objects of this research. The main objective is to understand the project of society transformation taking the author s criticism to the current system based on the aesthetics and psychoanalysis as the starting point. The investigation begins with the understanding of the origin of society and it tries to explicit both the repressed individual and the repressive society. Marcuse turns to Freud in order to back up his phylogenetic and ontogenetic arguments. The author shows the political characteristic of Freud and the first chapter is about this aspect. It is also necessary to understand both society and the one-dimensional man and what Marcuse suggests with the expression one-dimensional philosophy . In the second chapter, the influence of work, merchandise and language over man will be analyzed. In what follows, it is important to understand how the philosopher perceives art as a revolutionary object to emancipate society and what its real function for the one-dimensional society is. That is the reason why the third chapter will be specifically dedicated to the study of the Marcusean concept of art. The following concepts will be explicit: art in the affirmative culture, contemporary art, art in the one-dimensional society, the social role of art, Marxist aesthetics, the aesthetic dimension principles. The fourth chapter ponders the political principles to a revolution through art. When presenting the political principles, it is possible to understand Marcuse s project that he called The New Left. Therefore, presenting all of the arguments that support The New Left is a revolutionary political project that makes the emancipation of society possible.